Analysis of Teachers' Ability to Understand Early Childhood Development Based on Educational Backgrounds - Rahmi, Fanisa Aulia; Darsinah, D (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Early childhood education lays the groundwork for children’s lifelong learning, and teachers’ grasp of developmental stages is critical to program quality. This study examines whether teachers’ understanding of early childhood development differs according to their educational backgrounds in Sawit District, Boyolali Regency. Methodology: A quantitative descriptive design was adopted. The population comprised 96 early‑childhood educators affiliated with IGTKI and HIMPAUDI. Participants reported their highest qualification—ranging from D1, D3, non‑PAUD bachelor’s, PAUD bachelor’s, to high‑school equivalent—and completed a standardized assessment measuring knowledge of child‑development theory. Data were analyzed using the Mann–Whitney U test to compare score distributions across educational groups. Results: Statistical analysis revealed significant differences in developmental‑theory comprehension based on educational attainment (p < 0.05). The highest average score (20.54) was achieved by PAUD‑specialized bachelor’s graduates, followed by high‑school/equivalent teachers (18.70), non‑PAUD bachelor’s (18.09), D3 (18.00), and D1 (15.50) holders. These findings indicate that teachers with formal early‑childhood training demonstrate stronger theoretical understanding than those without specialized qualifications. Applications/Originality/Value: By mapping how educational background correlates with theoretical knowledge, this study highlights the need to tailor professional‑development programs to bridge gaps among educators. Its insights can guide district policymakers and training providers in designing targeted workshops and certification pathways, ensuring all early‑childhood teachers—regardless of prior qualification—attain the competencies necessary to support optimal child development.